Nazismen i Sverige - Berggren, Lena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
When doing scientific research on nazism as a historical and political phenomenon, one ought first attempt to clarify its ideological content. Nazism is a totalitarian, elitist and anti-democratic ideology which has as its absolute foundation a race-ideology where anti-semitism is a very important component. Nazism does, however, differ from the related ideologies fascism and right-wing extremism on some crucial points, one of them being that the latter two are not necessarily based on a race-ideology. The first Swedish nazi party was established in 1924 and was called the Swedish National Federation of Liberty (Svenska Nationalsocialistiska Frihetsförbundet). This was to be the beginning of a motley history of organisation where different forms of nazi parties as well as fascist and right-wing extremist organisations would flourish in Sweden. The Swedish "national movement" reached its numerical peak in the middle of the 1930’s when there was a total of 70 000 members, of which 40 000 belonged to the right-wing extremist National Federation of Sweden (Sveriges Nationella Förbund). The leading Swedish nazi party during the late 30’s and the 40’s, was NSAP/SSS, also known as the Lindholm Movement. This party was formed in 1933 and had its ideological roots in earlier Swedish nazi and fascist parties, but also in a long-standing native tradition of organized anti-semitism. The party was not closed down until 1950.